La política chilena de concesiones viales: ¿mimetismo o singularidad institucional? - Sabah Zrari (Nuevo mundo - Mundos Nuevos, 2008)
The public policy regarding public infrastructure licensing in Chile since the nineties does not merely correspond to the influence of foreign models. It is better characterized by singularities whose origin lies in the history of Chilean roads and the relation between the public and private sectors.   These singularities are explained by the beliefs and norms regarding the role of the State in the country's development, and about infrastructure as key to that development. The latter does not imply that foreign influence was completely absent, but explains that its design and implementation differ in certain areas, such as regulation, from the "good practices" promoted by some international organizations.